Song of Songs and the charism of Mother Theresa of Calcutta (Cant 1:5-2:17) - Bardski, Krzysztof (Warszawskie Studia Teologiczne, 2019)
The ancient Christian tradition considered the allegorical interpretation of the Bible as an important mean of spiritual formation in the life of the Church. This approach to the Biblical text has been neglected in modern times due to the use of historical-critical methods in the Biblical exegesis. However, it seems that the intuitions of the Fathers of the Church may still be inspiring, especially for certain spiritual actualizations of the Scripture. In some contexts of the life of the Church, e.g. spiritual retreats, the symbolical and allegorical reading of the Bible can be still fruitful, especially in connection with new spiritualties emerging in modern times. Even more, the access to critical editions of patristic works and the semiotic approach to the Biblical text make possible new understandings that may enrich the living tradition of Biblical interpretation.